Age at first anal sex and HIV/STI vulnerability among gay men in Australia. Issue 4 (12th January 2012) - Lyons, Anthony; Pitts, Marian; Grierson, Jeffrey; Smith, Anthony; McNally, Stephen; Couch, Murray
Abstract : Objectives: To determine whether there is a link between age at first anal intercourse (AFAI) and gay men's HIV/sexually transmissible infection (STI) vulnerability, including tendencies to engage in higher risk sexual behaviour. Methods: A nationwide cross-sectional survey was conducted online involving 845 Australian gay men born between 1944 and 1993. Results: Median AFAI fell from 35 years for men born between 1944 and 1953 to 18 years for men born between 1984 and 1993. Of those who reported having had anal intercourse (N=822), HIV-positive men were found to be significantly younger on average when they first had anal intercourse compared with HIV-negative men (18.5 vs 21.3 years, p<0.001). Men with a history of other STIs were also significantly younger. Engaging in higher risk sexual behaviour is a likely factor, with AFAI generally younger among men who reported >10 sexual partners in the past year (p<0.001) and who engaged in group sex (p<0.001), receptive anal intercourse (p=0.008) or were drug or alcohol affected (p=0.06) during their most recent sexual encounter. Conclusions: There appears to be a strong link between AFAI and infection with HIV/STIs, as well as tendencies to engage in higher risk sexual behaviour. While further research is needed to understand this link, these findings highlight a need for sexuality education aimed at gay-identified youth to ensure their sexual debut does not lead to poorer sexual health outcomes.